SPATIAL PLANNING LEGISLATION IN GHANA: EXPLORING THE EVOLUTION, CONTRIBUTIONS, AND THE WAY FORWARD. - Sarfo, A. K. (UDS International Journal of Development, 2021)
This paper explored the evolution of spatial planning in Ghanaâ€™s context. Using Institutional Analytical Framework, the paper posits that spatial planning has gone through several changes over the years. Additionally, it was revealed that spatial planning as an idea dates back to nineteenth-century industrialization and urbanization that mostly happened in developed countries. These had less focus on civic design and came to be more competent in state policy. Although planning in Ghana antedates the early 90s, nationwide spatial planning commenced with the preparation and initiation of CAP 84 (Town and Country Planning Ordinance) in 1945. Fast forward spatial planning in Ghana is presently being done by tenets and provisions as captured in Act 925 - Land Use and Spatial Planning Act 2016. However, this paper establishes possible conflict and duplication of planning efforts and practices by looking at Act 925 and Act 480 - National Development Planning System Act, 1994. It envisages that planning in Ghana will go through another evolution to avert the â€œspatialâ€ and â€œpolicyâ€ perspectives to planning and as well attain coordinated efforts to guide the course of planning in Ghana. Keywords: Spatial planning, Land use, Evolution, Planning conflict